Inecuaciones interactivas en la web - Corrales-Z, Lizeth; Picado-M, María José; Ramírez-A, Jasiel; Reyes-F, Yerlin (My University, 2022)
Se aprenderá inecuaciones con actividades lúdicas por medio del software Mathigon.

Inequalities will be learned with recreational activities through the Mathigon software.
Keywords: Desigualdades; Matemáticas; Software Mathigon; Álgebra; Educación -- Actividades; Aprendizaje lúdico; Inequalities; Mathematics; Education -- Activities; Playful learning